The Influence of Social Media, Product Quality, and Price on Purchasing Decisions on UMKM Ayra & Eve in Surabaya - Weni Widiasti Ningrum; I Nyoman Sudapet; Hamzah Denny Subagio (LPPM NAROTAMA UNIVERSITY, Indonesia, 2018)
Purchasing decisions are very important. Because a product will be sold, with a purchase decision made by consumers. As with the UMKM Ayra & Eve in Surabaya, the more purchasing decisions made by consumers, the more products are sold. In this study to analyze the influence of social media, product quality, price on purchasing decisions. This study uses quantitative research with a sample of 80 respondents. And data were analyzed using multiple linear regression analysis techniques and classical assumption tests. Simultaneous social media, product quality, and significant price for purchasing decisions. Therefore, the UMKM Ayra&Eve in Surabaya must be maintained.